PENGARUH VARIASI KOMPOSISI SELULOSA JERAMI PADI DAN LIMBAH BOTOL PLASTIK POLIETILEN TEREFTALAT (PET) TERHADAP KARAKTERISTIK BIODEGRADABLE PLASTIC - Hanna Sjafarina; Intan Syahbanu; Nurlina Nurlina (Tanjungpura University, 2020)
Research on the effect of variations in the composition of rice straw cellulose on the characteristics of biodegradable PET-Cellulose plastic. The purpose of this study is to explain the effect of the composition of rice straw cellulose and PET on the characteristics of biodegradable plastic made from composite of rice straw cellulose and PET. This research was conducted in several stages, the isolation of cellulose from rice straw, recycling PET from mineral water bottle, mixing cellulose and PET, then testing the characteristics, the DTA-TGA thermal characteristic test, and degradation test with the soil burial test method. . In the thermal characteristics test there was a decrease in weight in samples with composition PET: cellulose 90:10; 60:40; and 50:50 each with 0.719; 0.710; 0.581 mg in the temperature range 38.30-68.32 ° C, 40.72-68.17 ° C, 41.45-80.40 ° C, while in the samples 80:20 and 70:30 there was no decrease in weight the temperature. In the sample 90:10; 80:20; 70:30; 60:40 and 50; 50 there is a decrease in weight each of 4,045; 3,909; 3,464; 2,760 and 3,205 mg at temperatures 328, 16-430.65 ° C, 362.05-442.15 ° C, 349.96-439.82 ° C, 388.29-446.70 ° C, and 325.39-420.79 ° C. The degradation test using soil burial test method obtained percent weight loss in samples with PET composition: 70:30 cellulose which was 38.24%.